Carbonation of calcium sulfoaluminate mortars. (July 2017) - Hargis, Craig W.; Lothenbach, Barbara; Müller, Christian J.; Winnefeld, Frank
Abstract: This study investigated potential physical and chemical parameters that could govern the carbonation rate of calcium sulfoaluminate (CSA) mortars and endeavored to elucidate the microstructural and chemical factors that govern CSA cement's carbonation rate. Experiments included: water absorption, oxygen diffusion, mercury intrusion porosimetry, quantitative X-ray diffraction, thermogravimetric analysis, accelerated carbonation, compression and flexure tests. Additionally, the carbonation process was investigated using thermodynamic modeling. The results show that CSA mortars carbonate much faster than Portland cement mortars and at approximately the same rate as calcium aluminate cement mortars. Additionally, CSA mortars carbonate slower with decreasing w/c, and the anhydrite content of the CSA mortars strongly affects the ye'elimite reaction kinetics which plays an important role in imparting carbonation resistance in CSA mortars. Finally, calcium sulfate additions to CSA clinker to produce CSA cement dilutes the clinker content and reduces the amount of CO2 that the CSA cement can ultimately bind.